Lag coefficient of Bimetal Thermometer of Chronometric type Radiosonde (Model 2) (MAUSAM, 1961)
The lag coefficient of the bimetal thermometer element as used in chronometric radiosonde of India Meteorological Department has been calculated with the help of the difference in temperatures obtained from a radiosonde during its ascent and descent. The average lag in the recorded temperature has also been calculated.